A Rare Cause of Hemoptysis in a Chronic Obstructive Pulmonary Disease Patient - M. Mahendra; M. T. Rashmitha; Santosh Patil (APIK Journal of Internal Medicine, 2025)
Strongyloides stercoralis is an intestinal nematode with both free-living and parasitic stages and is common in the tropics. We present the case of a 65-year-old male presented with breathlessness, productive cough, hemoptysis, and fever and admitted with provisional diagnosis of acute exacerbation of chronic obstructive pulmonary disease. Sputum investigations were sent and showed rhabditiform larva of S. stercoralis, and the screening test for HIV antibody was negative. Other laboratory parameters were within the normal limits. His chest computed tomography showed centrilobular nodules and paraseptal emphysematous changes. He was thereby diagnosed to be a case of pulmonary hyperinfection strongyloidiasis and started on ivermectin and albendazole in addition to antibiotics, his respiratory symptoms improved, and S. stercoralis was not detected in subsequent follow-up examinations thereafter.